Strategi pengembangan bisnis PT XYZ sebagai penyedia cetak dengan pendekatan Business Model Canvas (BMC) - Laksono, Alifsyah; Zulkarnain; Fitria Utami, Adita Evalina (Journal of Economics, Business, Accounting and Management, 2025)
This study analyzes the business model of PT XYZ, an offset and digital printing company, using the BMC approach and formulates business development strategies through SWOT analysis and the AHP. The company has experienced stagnant sales due to market changes, intense competition, the impact of the pandemic, and technological advancements. SWOT analysis identified 15 strategic factors, and the SWOT-AHP results placed the company in Quadrant I of the Grand Strategy Matrix, indicating a progressive condition. The main strategies prioritized include strengthening partnerships, reducing reliance on offset printing, and optimizing the use of printing equipment. These strategies are mapped into the BMC framework, focusing on customer segments (SMEs, election institutions), value propositions (high-quality products, custom packaging services), distribution channels, customer relationships, key activities, key resources, and key partnerships. The findings provide strategic direction for PT XYZ to enhance its competitiveness through a structured and adaptive business model improvement.